Annual needs in conversion power and digestible a protein cows with yield of milk from 5000 to 9000 kg - Трончук, І. С.; Рак, Т. М. (Scientific Progress & Innovations, 2012)
It is generalized theoretical bases and a modern advanced experience of feeding of highly productive cows. On the basis lactation curve yields of milk for a lactation daily yields of milk, monthly and annual requirement for nutrients are defined. It is established that annual requirement in exchange energy cows with a yield of milk of 5000 kg is 57119 МDg, at 7000 kg – 69430, at 9000 kg – 84363 МDg, in digestible a protein accordingly 495,17; 643,68 and 790,35 kg. It is specified structure of diets in percentage of their feeding power and on the basis of these indicators the annual requirement for forages is defined. In particular annual requirement for the concentrated forages (combined feed-concentrates with feeding power of 1 kg not below 10,5 МDg ) at yields of milk of milk of 5000 kg is 14,17 c, at 7000 kg – 21,24 and at 9000 kg – 31,31 c.